RUMAH ORKESTRA JOGJA SEBAGAI WAHANA KREATIVITAS DALAM MENUMBUHKAN ETOS KERJA DAN KOLEKTIVITAS BAGI ANAK SEKOLAH DASAR - Dhyanindra, Fransiska Dhamma; Masseleng, Manda Marindaa; Candra Kartika, Hedwigis Nada; de Fretes, Daniel (JURNAL PAKARENA, 2025)
As a magical art medium, music contains values that grow in the souls of music enthusiasts. This study aims to analyze the strategy of Rumah Orkestra Jogja (ROJ) in fostering an independent work ethic and collectivity in elementary school children. This study also explores children's musical experiences in ROJ as a non-formal music learning community. The research method used is a qualitative approach with case studies. Data were collected through interviews, observations, and documentation of community members, trainers, and parents. The study results show that ROJ has succeeded in forming an inclusive learning space and supporting the development of children's social and musical skills through creative approaches, such as thematic concerts and fun practice programs. Collective experiences in music at ROJ improve technical competence and build discipline, responsibility, and the ability to work together.